IMPROVING STUDENTS’ PARTICIPATION IN LEARNING READING COMPREHENSION OF NARRATIVE TEXTS THROUGH CONSTRUCTIVE READING MODEL (CRM) (Language Circle: Journal of Language and Literature, 2013)
This article is a report of an action research project conducted in reading class for Eleventh Year Students of State Senior High School 7 Cirebon in the Academic Year of 2012/2013. The objectives of this study are to describe: (1) the problems faced by the students  in learning reading comprehension  (2)  how  Constructive Reading Model is implemented (3) whether Constructive Reading Model improve students’ participation in learning reading  comprehension . The result from the questionnaires and observation sheet showed that(1) the students  did not actively participate in the process of teaching learning, (2) by using Constructive Reading Model  students’ participation from pre-cycle to cycle 1 increased , from cycle 1 to cycle 2 increased,  and (3)  students’ score of  reading comprehension  from pre-cycle to cycle 1 increased 15.65 points, from cycle 1 to cycle 2 increased 11.59 points. So  the study concluded that the implementation of Constructive Reading Model  (1) could solve the problems faced by the students in learning reading comprehension (2) could improve students’ participation in the process of teaching learning  and(3) could develop students’  reading comprehension mastery of the Eleventh Year Students of State Senior High School 7 Cirebon.